Creating Cherokee Print: Samuel Austin Worcester’s Impact on the Syllabary - Thomas, William Joseph (East Carolina University, 2008)
The 1821 creation of a written syllabary for the Cherokee language by Sequoyah and its use in the Nation’s newspaper, the Cherokee Phoenix, are routinely examined within the context of the tribe’s discourse surrounding removal in the 1830s, but scholars often overlook the influence of the missionary Samuel Austin Worcester and the American Board of Commissioners for Foreign Missions (ABCFM) in shaping the parameters of that discourse by arranging the syllabary, typesetting the characters, and establishing the press. This article illuminates these significant historical and technical aspects of Worcester’s influence on the creation of Cherokee print. Worcester’s influence on the Cherokee syllabary is important, given the enduring nature of his influence and the rapid adoption of the written language: within fourteen years of its introduction, and seven years of the first printing, more than half of all households in the Cherokee Nation had a reader of Cherokee. Today, nearly 180 years after Worcester first standardized Cherokee characters in print, his forms of the syllabic characters guide instruction in reading and writing Cherokee, and his translation of the Bible into Cherokee persists in Cherokee homes.
Keywords: Worcester, Samuel Austin; Cherokee syllabary; American Board of Commissioners for Foreign Missions